Equalizing access: affirmative action in higher education in India, United States, and South Africa - Hasan, Zoya; Nussbaum, Martha C. (New Delhi: Oxford University Press, 2012)
Papers presented at a conference on 'Affirmative action in higher education in India, United States, and South Africa', held at New Delhi in March 2008.
Includes bibliographical references.
Keywords: AFFIRMATIVE ACTION PROGRAMS IN EDUCATION-INDIA; AFFIRMATIVE ACTION PROGRAMS IN EDUCATION--SOUTH AFRICA